Caminhos, encruzilhadas, porteiras e feitiços para uma filosofia popular brasileira - Rafael Haddock-Lobo (Comparative Cultural Studies, 2022)
This article aims to present some reflections on certain aspects presents in the relationship between Brazilian popular philosophy and the macumbas (a set of religious activities that arise from the cross between the cultures of the African diaspora, the knowledge of the original peoples, and the popular Portuguese Catholicism). In this sense, at first, we will start from the notion of experience, which needs to be revisited in the light of popular knowledges in order to rethink the very notion of method. Method, then, no longer thought only as the opening of the path (as Descartes), in which the philosopher shows that there is only one to be followed, but thought from the wisdom of the forests, where the footsteps of the caboclos show us that every path is made for walking. Thus, more than a method, it seems that the question makes us rethink whether it is not “style” that we are dealing with or what we should need to deal with: the way we enchant and chant our spells so that philosophy no longer arrives loaded with the weight of a coloniality that only seems to paralyze us, like prey in front of the predator’s seductive gaze.